Responses to Hypoxia and Endoplasmic Reticulum Stress Discriminate the Development of Vitreous and Floury Endosperms of Conventional Maize (Zea mays) Inbred Lines - Gayral, Mathieu; Elmorjani, Khalil; Dalgalarrondo, Michèle; Balzergue, Sandrine M.; Pateyron, Stéphanie; Morel, Marie-Hélène; Brunet, Sylvie; Linossier, Laurent; Delluc, Caroline; Bakan, Bénédicte; Marion, Didier (Frontiers in Plant Science, 2017)
Major nutritional and agronomical issues relating to maize (Zea mays) grains depend on the vitreousness/hardness of its endosperm. To identify the corresponding molecular and cellular mechanisms, most studies have been conducted on opaque/floury mutants, and recently on Quality Protein Maize, a reversion of an opaque2 mutation by modifier genes. These mutant lines are far from conventional maize crops. Therefore, a dent and a flint inbred line were chosen for analysis of the transcriptome, amino acid, and sugar metabolites of developing central and peripheral endosperm that is, the forthcoming floury and vitreous regions of mature seeds, respectively. The results suggested that the formation of endosperm vitreousness is clearly associated with significant differences in the responses of the endosperm to hypoxia and endoplasmic reticulum stress. This occurs through a coordinated regulation of energy metabolism and storage protein (i.e. zein) biosynthesis during the grain-filling period. Indeed, genes involved in the glycolysis and tricarboxylic acid cycle are up-regulated in the periphery, while transcriptomic and metabolomic analyses suggest that the fermentative metabolism prevails in the endosperm center. This spatial metabolic regulation allows the production of ATP needed for the significant zein synthesis that occurs at the endosperm periphery; this finding agrees with the zein-decreasing gradient previously observed from the sub-aleurone layer to the endosperm center. The massive synthesis of proteins transiting through endoplasmic reticulum elicits the unfolded protein responses, as indicated by the splicing of bZip60 transcription factor. This splicing is relatively higher at the center of the endosperm than at its periphery. The biological responses associated with this developmental stress, which control the starch/protein balance, leading ultimately to the formation of the vitreous and floury regions of mature endosperm, are discussed.